Gas-liquid and liquid-liquid separators - Stewart, Maurice (Elsevier [u.a.], 2009)
This practical guide is designed to help engineers and operators develop a 'feel' for selection, specification, operating parameters, and trouble-shooting separators; form an understanding of the uncertainties and assumptions inherent in operating the equipment. The goal is to help familiarize operators with the knowledge and tools required to understand design flaws and solve everyday operational problems for types of separators
Includes bibliographical references and index
Keywords: Gases -- Separation.; Separators (Machines); elektronické knihy; electronic books